PEMBINAAN SANTRI DAN SANTRIWATI DALAM MENINGKATKAN PRESTASI MUSABAQAH QIRA’ATUL KUTUB NASIONAL (MQKN) DI PONDOK PESANTREN DARUSSALIM BATI-BATI - Helda, Nor; Ramli, Muhamad (ADDABANA: Jurnal Pendidikan Agama Islam, 2024)
Abstract: This research discusses the development of Santri and female students in improving the achievements of the National Musabaqah Qira'atil Kutub (MQKN) at the Darussalim Bati-Bati Islamic Boarding School. This research aims to describe the development of santri and female students in improving the achievements of the National Musabaqah Qira'atil Kutub (MQKN) at the Darussalim Bati-Bati Islamic boarding school, as well as the supporting and inhibiting factors. In extracting data, researchers used observation, interview, and documentation techniques. The development of Islamic boarding school students and female students in improving the achievements of the National Musabaqah Qira'ati Kutub (MQKN) at the Darussalim Bati-Bati Islamic Boarding School has been carried out well, it can be seen starting from program planning, program implementation, and program supervision. Planning is carried out starting from the selection of assisted students and female students, supervisory teachers, coaching time, and schedule. The implementation of the coaching program is realized through curricular and extracurricular activities. Supervision is carried out in stages, starting from the head of the boarding school, the head of the supervisor, and the supervisor to the parents of the students and female students. Supporting factors in this training are the guidance teacher, the physical and psychological condition of the students, the intelligence and talents of the students, frequent training, and collaboration with parents. The inhibiting factors are inadequate time management and facilities. Keywords: Development, Learning Achievement, Islamic Boarding School, Yellow                             Book. Abstrak: Penelitian ini membahas tentang pembinaan santri dan santriwati dalam meningkatkan prestasi Musabaqah Qira’atil Kutub Nasional (MQKN) di Pondok Pesantren Darussalim Bati-Bati. Tujuan penelitian ini adalah untuk mendeskripsikan pembinaan santri dan santriwati dalam peningkatan prestasi Musabaqah Qira’atil Kutub Nasional (MQKN) di pondok pesantren Darussalim Bati-Bati, serta faktor pendukung dan penghambatnya. Dalam penggalian data, peneliti menggunakan teknik observasi, wawancara dan dokumentasi. Pembinaan santri dan santriwati dalam meningkatkan prestasi Musabaqah Qira’ati Kutub Nasional (MQKN) di Pondok Pesantren Darussalim Bati-Bati telah terlaksana dengan baik, dapat dilihat mulai dari perencanaan program, pelaksanaan program dan pengawasan program. Perencanaan dilakukan mulai dari pemilihan santri dan santriwati binaan, guru pembina, waktu dan jadwal pembinaan. Pelaksanaan program pembinaan direalisasikan melalui kegiatan kurikuler dan ekstrakurikuler. Adapun pengawasan dilakukan secara berjenjang, mulai dari pimpinan pondok, ketua pembina, guru pembina hingga orang tua santri dan santriwati. Faktor pendukung dalam pembiaan ini adalah guru pembina, keadaan fisik dan psikis santri, kecerdasan dan bakat santri, sering melakukan latihan dan kerjasama dengan orang tua. Adapun faktor penghambat adalah pengelolaan waktu dan fasilitas yang belum memadai.Kata Kunci: Pembinaan, Prestasi Belajar, Pondok Pesantren, Kitab Kuning.